The role of hyperlocal media in cultural preservation: an analysis of the Three Cs implementation at Galuh Prambanan TV in Klaten - Jati, Rocky Prasetyo (International Journal of Visual and Performing Arts, 2024)
This paper explores implementing the "Three Cs" principles (Community, Commitment, and Continuity) proposed by Agnes Gulyas and Kristy Hess within the context of hyperlocal media as a cultural preservation. A case study was conducted on Galuh Prambanan TV in Klaten, a local media outlet focused on Javanese cultural content. The research employs a qualitative approach by gathering data through in-depth interviews, direct observation, and case study analysis. The primary informants in this research are media practitioners and local cultural figures. The findings indicate that local community engagement is crucial in ensuring cultural preservation. The community's long-term commitment to the production and consumption of local cultural content is also a critical factor in the success of this preservation. Continuity in the presentation and management of content through applying the hyperlocal media model, as demonstrated by Galuh Prambanan TV, enables operational sustainability and strengthens relationships with the community. Implementing these principles positions Galuh Prambanan TV as an active agent in preserving Javanese culture while providing an example of how hyperlocal media can support cultural preservation in the face of globalization and modernization challenges. Therefore, this study concludes that applying the "Three Cs" is crucial for the sustainability of hyperlocal media and the successful preservation of local culture. Consequently, this research provides practical contributions to developing more effective cultural preservation strategies through hyperlocal media.